Persepsi guru mengenai mata pelajaran IPAS pada kurikulum merdeka di kelas IV sekolah dasar - Annisa Noor Hidayah; Rukayah Rukayah; Supianto Supianto (Didaktika Dwija Indria, 2024)
The aim of this research is to describe teachers' perceptions of science and science subjects in the independent curriculum in class IV of SD Negeri Bratan 1. This research uses qualitative methods with a case study approach. Primary data was obtained from interviews and questionnaires with class IV homeroom teachers, while secondary data used documentation. The research sampling technique used purposive sampling technique. Validate the data through technical triangulation and source triangulation. Employ the Miles and Huberman model as the selected method for data analysis, encompassing data collection, reduction, presentation, and conclusion drawing. The results of the research show a positive response from teachers towards the independent curriculum in class IV science subjects. Teachers understand IPAS as a combination of science and social studies which aims to develop students' potential based on interests and talents. The introduction of the independent curriculum in IPAS results in notable alterations to the content, teaching approach, teacher role, and student activity. Teachers consider student involvement as the key to success in the IPAS assessment. Teacher perceptions reflect efforts to create learning experiences that support student involvement, and teachers are considered ready to carry out science learning with thorough understanding, planning, application and assessment.